Multivisceral transplantation of pelvic organs in rats - Galvao, Flavio Henrique Ferreira; Araki, Jun; Fonseca, Ana Bruna Salles; Cruz, Ruy Jorge; Lanchotte, Cinthia; Waisberg, Daniel Reis; Chaib, Eleazar; Nacif, Lucas Souto; Traldi, Maria Clara de Camargo; Mello, Estrella Bianco de; Andraus, Wellington; Carneiro-D'Albuquerque, Luiz (Frontiers in Surgery, 2023)
Multivisceral transplantation of pelvic organs would be a potential treatment for severe pelvic floor dysfunction with fecal and urinary incontinence, extensive perineal trauma or congenital disorders. Here, we describe the microsurgical technique of multivisceral transplantation of pelvic organs, including the pelvic floor, in rats. Donor operation – We performed a perineal (including genitalia, anus, muscles and ligaments) and abdominal incision. The dissection progressed near the pelvic ring, dividing ligaments, muscles, external iliac vessels and pudendal nerves, allowing the pelvic floor mobilization. The aorta and vena cava were isolated distally, preserving the internal iliac and gonadal vessels. The graft containing skin, muscles, ligaments, bladder, ureter, rectum, anus and vagina, uterus and ovarian or penile, testis and its ducts is en bloc removed, flushed and cold stored. Recipient operation – The infrarenal aorta and vena cava were isolated and donor/recipient aorta-aorta and cava-cava end-to-side microanastomoses were performed. After pelvic floor and viscera removal, we performed microanastomoses between donor and recipient ureter, rectum and pudenda nerves. The pelvic floor was repositioned in its original position (orthotopic model) or in the abdominal wall (heterotopic model). We sacrificed the animals two hours after surgery. Results - We performed seven orthotopic and four heterotopic transplantations. One animal from orthotopic model and one from heterotopic model died due to technical failure. Six orthotopic and three heterotopic recipients survived up to 2 hours after transplantation. Conclusion- The microsurgical technique for pelvic floor transplantation in rats is feasible, reaching an early survival rate of 81.82%.